ANALISIS REFORMASI KEPEGAWAIAN (STUDI PELAKSANAAN SELEKSI TERBUKA JABATAN PIMPINAN TINGGI PRATAMA (JPT) BERBASIS MERIT SISTEM PADA PEMERINTAH DAERAH KABUPATEN INDRAGIRI HILIR) - Muammar Alkadafi; Ria Rahmadani; Hendry Andry (UIR Press, 2018)
One important aspect of staffing reform is the promotion system of civil state apparatus publicly and competitively within the local government, in high leadership positions (JPT) pratama or positions equalized with structural positions echelon II.b and a. The Local Government of Indragiri Hilir Regency through the Regional Personnel Board has conducted an open promotion on the filling of the Primary Leadership Position, for the first time in 2015. The purpose of this study is to analyze the personnel reform based on system merit in the implementation of the selection of Primary Charge in the local government of Regency Indragiri Hilir. The research method used is descriptive research method with qualitative data analysis approach by using data analysis according to Miles and Huberman namely; data reduction, data presentation and conclusion. The sources in this research are Selection Committee, secretariat of selection committee, selection of JPT Pratama, Civil Servant at Local Government of Indragiri Hilir Regency. In this study the authors use data collection methods using observation, interviews, and documentation. The results of the study show that personnel reform in the implementation of the selection of Primary Charge to the local government of Indragiri Hili Regency is seen from the aspect of preparation, implementation and monitoring and evaluation as stipulated in the provisions of Permenpan-RB no. 13 Year 2014, mechanically and procedurally has been implemented in accordance with the provisions. From the result of data analysis of implementation and recommendation from KASN to the selection implementation process, implicitly can be concluded that the implementation process contains the principles of objectivity, competitive, transparency and accountability in every stage process conducted by selection committee to 5 (five) .The consideration of qualifications, competence and performance (merit system) on the determination of graduation in general has become the consideration of the selection committee. For the next selection process by appraising the assessment center, the authors suggest that the preparation of competency standards in detail and detail, success criteria from office, the selection material should be more directed to the task and function metrics of each position, the selection method is more directed to a deep observation of the behavior of officials, and conduct a thorough evaluation of the potential, potential, strength and weaknesses of the candidate, a relevant to the effectiveness of a desired organization.